Optymalizacyjny model planowania rozwoju zasobów wykwalifikowanej siły roboczej w okresie perspektywicznym - Dymarski, Włodzimierz (Wydział Prawa i Administracji UAM, 1972)
This paper is an attempt to relate the qualified manpower resources development to the economic development in a linear optimization model. The essence of the model is a simultaneous optimization of investment both in physical and human capital. The author assumes that the question can be reduced to optimization of the set of production techniques. Reducing substitutability of particular factors of production to substitutability of the whole groups of factors, the model takes into account its technological limitations. In the long-term perspective, education appears the strategic factor of qualified manpower resources development. Thus in the model the problem of investment in human capital is reduced to inputs in education, and the level of skills is, in principle, identified with the level of education. The model includes various institutional forms of education and training, also adult education joined or not with a part-time employment. The objective function of the model is the maximization of the final product for non-investment purposes in the whole planning period (with a required aggregate composition given every year), subject to several balance constrains and to required minimal year-by-year rates of its own growth and the growth of the average level of education of manpower. The terminal conditions relating to education and investment in physical capital are the exogenous variables of the model.
An Optimization Model of Planning Qualified Manpower Resources Development over a Long-Term Perspective